Synthesis and characterization of ZnO flower-like structures. Issue 1 (2nd January 2016) - Sharma, Shatendra; Sharma, Yogita; Sharma, Jyotsna
Abstract: The flower-like ZnO nanorods have been successfully synthesized by a surfactant-assisted hydrothermal method. The nanostructures formed by ZnO nanorods were synthesized and deposited without seeding in glass flask by a hexamethylenetetramine (HMTA)-assisted hydrothermal method at low temperature with NaOH as surfactant and catalyst. The synthesized ZnO flowers comprise of several spike structures that have hexagonal cross section and taper toward the end. The structures are investigated using X-ray diffraction, scanning electron microscope and transmission microscope. The optical properties are studied with UV-VIS, FTIR, and Raman spectroscopy. The process of synthesis is simple and highly reproducible. The synthesized flower-like structures are suitable for use as sensors applications.